HPB O05 Identifying pathways involved in post-hepatectomy liver failure. (7th December 2022) - Rehman, Adeeb; Copple, Ian; Jones, Robert; Diaz-Nieto, Rafael; Malik, Hassan; Fenwick, Stephen
Abstract: Background: The liver is the only visceral organ with regenerative capabilities. This ensures maintenance of the liver-to-bodyweight ratio required for homeostasis. Failure of this mechanism can be fatal. Precipitants to liver failure include infection, drug toxicity and surgical resection. Post-hepatectomy liver failure (PHLF) is associated with small for size syndrome i.e., insufficient post hepatectomy liver volume. The mechanisms by which liver failure occurs on a molecular basis are not yet fully understood, but theories include uncontrolled apoptosis from unrivalled superoxide radical formation causing irreparable oxidative stress. A major research focus of liver regeneration has been modulating the anti-oxidative response to any form of liver injury, but identifying pathways involved in dysfunctional liver regeneration after surgery have yet to be elucidated. Nuclear factor erythoid 2-related factor 2 (Nrf2) is an anti-oxidant transcription factor which promotes liver regeneration. Using a murine partial hepatectomy model, we have shown that pharmacological stimulation of Nrf2 increases the rate of post hepatectomy liver regeneration. Furthermore glutathione (GSH – a downstream target of Nrf2), has been linked with impaired liver regeneration when deficient. In this study, we present data on GSH analysis in liver tissue taken from patients undergoing hepatectomy. Methods: Liver parenchyma was collected ex-vivo from patients undergoing liver resection (National Research Ethics Service approval 11/NW/0327). Additionally, isolated RNA from hepatic parenchyma from patients undergoing liver resections was received from collaborators at the Medical University of Vienna, Austria. From liver tissue, protein was isolated using a standard protocol and immunoblotting performed; RNA was isolated using a Monarch RNA preparation kit (NEB, UK), and quantitative PCR was performed. GSH levels in liver tissue were analysed using a standard enzyme recycling method. Relevant targets were identified based on their response to anti-oxidative stress as defined in literature. Primers were designed based on internally validated sequences and antibodies were purchased externally. qPCR was performed using the fluorescent dye, SYBR Green with a ViiA 7 Real-Time PCR system (ThermoFisher). Immunoblotting consisted of transferring separated by weight proteins onto a membrane which was then blocked in 5% milk, with primary and then secondary antibody incubation. Chemiluminescence was applied and bands were visualised using a ChemiDoc (BioRad). Bands were quantified using ImageJ software, and expressed in relation to actin. PHLF was classified according to the ISGLS criteria. Control patients (with no PHLF) were matched for demographic and clinico-pathologic variables (major resection as per the Brisbane criteria). Results: Protein expression and GSH expression was measured in liver tissue from 23 patients. Of these, 10 had no PHLF, 4, 3 and 6 were classified as having Grades A, B, and C PHLF respectively. Additional isolated RNA samples yielded 11 with no PHLF, and 14 PHLF (4, 7 and 3, grade A, grade B and grade C, respectively) patients. A GSH assay showed no change in expression between those without PHLF and those with grade A and grade B, but patients who had grade C PHLF had significantly lower levels of GSH (p=0.0040). With respect to gene expression, GCLC, encoding the enzyme glutamate cysteine ligase catalytic subunit, the first rate limiting enzyme of glutathione synthesis, was also significantly lower in patients with grade C compared to those without PHLF of grade A/B (p=0.0206). Protein expression showed significantly reduced levels of GCLC when comparing grade C with patients without PHLF. Furthermore, samples taken at 2 timepoints (pre-parenchymal transection, and then 2 hours later from the resection margin) have shown a decrease in GCLC gene expression in patients who have grade C PHLF. Conclusions: Our results have shown that patients who have grade C PHLF (who all died from acute liver failure post-operatively), have significantly lower levels of GSH in liver tissue taken at the time of resection. There is already a weight of evidence showing activation of the transcription factor Nrf2 (encoding GSH) enhances liver regeneration, however this is not without off target effects. Although not known to promote oncogenesis, in vitro studies have shown that persistent overstimulation of Nrf2 promotes cancer cell growth and proliferation, in part by improving the chemoresistance of cancer cells. This effect is theorised to be due to metabolic reprogramming of cancer cells, resulting in elevated levels of metabolic enzymes involved in cell proliferation.Whilst it is appreciated that liver failure is multi-factorial, targeting genes that promote liver regeneration may reduce the risk of failure. Identifying and targeting individual genes which are involved in liver regeneration may help to overcome potentially deleterious off target effects. This data suggests that GSH is a potential therapeutic target reducing the risk of PHLF.